El maltrato infantil y su incidencia en el desarrollo socio-afectivo de las niñas y niños del primer año de educación general básica del centro educativo ¨Emiliano Abad¨ de la ciudad de Azogues, Provincia del Cañar, periodo 2014-2015 - Coronel Vasconez, Lida Yolanda (2015)
This thesis "CHILD ABUSE AND ITS IMPACT ON SOCIO-EMOTIONAL DEVELOPMENT OF CHILDREN FIRST YEAR OF BASIC EDUCATION GENERAL EDUCATION CENTER" EMILIO ABAD "AZOGUES CITY, PROVINCE OF CAÑAR, PERIOD 2014 - 2015" . It is a research project which has the general objective: To sensitize teachers, parents and parents about problems that can generate child abuse in the socio-emotional development. The methods used were: Inductive - deductive, descriptive, analytical and scientific techniques used were the survey and the Test Ebee León Gross, applied to parents the first year of basic education to establish the incidence of child abuse in the development socio-affective. In the survey of parents was obtained rates of child abuse more children are suffering insults and shouts with 80% rebuke to emotions such as sadness, joy, fear and shame 84%, not make threats activity 63%, beating his son when not obey an order by 67%, shaming the child in public when 85% is behaving badly, as seen children if they suffer psychological abuse by their parents. After application of the test to parents, it was determined that 55% of children are within the normal range for their age, 30%, parents should be alert to developments in the socio-emotional development, by ensuring that any delay in children and 15% of children are not developing properly, have behaviors and evidence they need psychological consultation must not occur.